ABCA1, TCF7, NFATC1, PRKCZ and PDGFA DNA methylation as potential epigenetic-sensitive targets in acute coronary syndrome via network analysis. (14th October 2021) - Infante, T; Franzese, M; Ruocco, A; Schiano, C; Affinito, O; Pane, K; Memoli, D; Rizzo, F; Weisz, A; Bontempo, P; Grimaldi, V; Berrino, L; et al.
Abstract: Background: Acute coronary syndrome (ACS) is the most severe clinical manifestation of coronary heart disease and the leading cause of death worldwide. Purpose: To perform an epigenome-wide analysis in circulating CD4+ and CD8+ T cells of ACS patients and healthy subjects (HS) enrolled in the DIANA clinical trial (NCT04371809) in order to identify differentially methylated genes (DMGs). Methods: Genomic DNA was extracted from CD4+ and CD8+ T cells of all subjects and sequenced by the reduced representation bisulfite sequencing (RRBS) platform. Functional pathway analysis was performed and significant DMGs were selected for gene expression validation by qRT-PCR in ACS patients and HS. GeneMANIA was used to built a prediction gene network. Correlation analyses between molecular data and clinical variables were performed. Results: In CD4+ T cells we identified 61 differentially methylated regions (DMRs) associated to 57 annotated genes of which 53% (n=32) were hyper- and 47% (n=29) were hypo-methylated in ACS patients vs HS. In CD8+ T cells we identified 613 DMRs associated to 569 annotated genes of which 28% (n=173) were hyper- and 72% (n=440) were hypo-methylated between two groups. In both cell type of ACS patients, 175 DMRs were associated to 157 annotated genes of which 41% (n=72) were hyper- and 59% (n=103) were hypo-methylated. From functional analysis, we selected the top 5 DMGs in the prevalent pathways with the highest differential of methylation values. Specifically, we considered 6 hub genes: NFATC1, TCF7, PDGFA, PRKCB, PRKCZ and ABCA1 and determined their respective expression levels by q-RT-PCR. We found a significant up-regulation of the selected genes in ACS patients vs HS (P<0.001 for all comparisons). Correlation analysis showed both common and cell specific correlation patterns. In CD4+ T cells, PDGFA promoter methylation was negatively correlated with CK-MB concentrations (r=−0.79, P=0.018). ABCA1, TCF7, PDGFA and PRKCZ gene expression was positively associated to CK-MB concentrations (r=0.75, P=0.03; r=0.760, P=0.029; r=0.72, P=0.044; r=0.74, P=0.035, respectively). Conlusions: This study is the first single-base resolution map of DNA methylome by RRBS in CD4+ and CD8+ T cells, providing specific methylation signatures that could help to clarify the role of aberrant methylation in ACS pathogenesis, and provide the basis for the search of novel epigenetic-sensitive biomarkers in the prevention and early diagnosis of this pathology. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Italian Ministry of Health;Italian Ministry of Research and University